Neonatal Hyperglycemia, which threshold value, diagnostic approach and treatment?: Turkish Neonatal and Pediatric Endocrinology and Diabetes Societies consensus report - Şimşek, Damla Gökşen (Turk Pediatri Ars, 2018)
Hyperglycemia has become an important risk factor for mortality and morbidity in the neonatal period, especially with increased survival rates of very low birth weight neonates. Hyperglycemia in the neonatal period develops as a result of various mechanisms including iatrogenic causes, inability to supress hepatic glucose production, insulin resistance or glucose intolerance, specifically in preterm neonates. Initiation of parenteral or enteral feeding in the early period in preterm babies increases insulin production and sensitivity. The plasma glucose is targeted to be kept between 70 and 150 mg/dL in the newborn baby. While a blood glucose value above 150 mg/dL is defined as hyperglycemia, blood glucose values measured with an interval of 4 hours of >180-200 mg/dL and +2 glucosuria require treatment. Although glucose infusion rate is reduced in treatment, use of insulin is recommended, if two blood glucose values measured with an interval of 4 hours are >250 mg/dL and glucosuria is present in two separate urine samples.